2014
DOI: 10.1111/opn.12074
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the influence of Internet‐based caregiver support on experiences of isolation for older spouse caregivers in rural areas: a qualitative interview study

Abstract: Internet-based services ought to be an option for caregiver support in rural areas as it may reduce feelings of isolation for older spouse caregivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 26 publications
1
36
0
9
Order By: Relevance
“…Six studies (43%) included qualitative outcomes. Blusi et al (), Blusi, Kristiansen, and Jong () used interviews in which they asked to participants to speak freely about their experiences of using internet‐based caregiver support. Lundberg () asked questions related to the caregivers’ appreciation of life.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six studies (43%) included qualitative outcomes. Blusi et al (), Blusi, Kristiansen, and Jong () used interviews in which they asked to participants to speak freely about their experiences of using internet‐based caregiver support. Lundberg () asked questions related to the caregivers’ appreciation of life.…”
Section: Resultsmentioning
confidence: 99%
“…Alves et al () in their intervention provided information in their sessions'; thanks to a professional expert on the theme of each session. Blusi et al (), Blusi et al () in their intervention provided information and educational software in order to ameliorate caregivers’ skills. The intervention of Danzl et al (), with the Kentucky Appalachian Rural Rehabilitation Network, aimed to disseminate information to caregivers of stroke survivors through verbal, visual and written methods.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, there may be a lack of resources to create and maintain formal in-person support groups in rural areas, particularly for individuals with MCI, which is a less commonly applied diagnosis than AD. Connecting with support groups via the Internet have been shown to reduce rural-dwelling caregiver’s feelings of isolation (Blusi, Kristiansen, & Jong, 2015), and should be considered as an option to improve social connections and build support systems where in-person support groups may not be possible or desirable. The Alzheimer’s Association also offers online message boards and chat rooms (Alzheimer’s Association, 2016) that allows for anonymity and accessibility for those with privacy or travel concerns.…”
Section: Discussionmentioning
confidence: 99%
“…One reason for including a control group in this study was to investigate if the highly positive outcome of previously published articles about e-health caregiver support may have other origins than the e-health service itself [10,15,16]. With the research in this article we wanted to inquire more deeply into usage patterns to find possible explanations.…”
Section: Discussionmentioning
confidence: 99%
“…A full description of the original study design and previous clinical results have been previously reported [10,15,16]. This study refers to long-term follow up after 1.5 years.…”
Section: Methodsmentioning
confidence: 99%